Maneras de ser y sentir. Una aproximación a la subjetividad de trabajadoras profesionales madres - Corsetti, Tania (El Colegio de México A.C., 2024)
This paper is preliminary research on the link between the exercise of motherhood and professional careers among women employed in private companies in the Greater Rosario metropolitan area, Argentina. A key element of this research is the subjectivity in the simultaneous exercise of motherhood and the professional employment, which constitutes a typical way of thinking, doing, and feeling of this study group. Using a qualitative methodology and Bourdieu’s habitus theory, I examine this simultaneity or dual presence/absence as a way of being, a predisposition to a set of practices aimed at performing professional work while taking on domestic tasks and o articulating both subfields, with the consequent self-denial. I also draw on anthropology of emotions to explore how this dual presence is felt, learned and expressed in these women’s bodies, while guiding daily practices and career paths, where a sense of being overwhelmed, exhausted and guilty constitutes much of the feeling-thinking corpus of these working mothers.